PENDAMPINGAN KONSULTASI DESAIN STRUKTUR ATAS GEDUNG GYS BANJARMASIN 6 LANTAI KOTA BANJARMASIN - Hadi Surya Wibawanto (Universitas Borneo Tarakan, 2022)
This Abdimas activity in the form of Science and Technology for the Community (IbM) is a structural design consultation assistance for the GYS (True Jesus Church) building in Banjarmasin City, South Kalimantan Province. This building is a center for educational activities and a place of worship for the people of Banjarmasin City. This building will be built with 6 floors functionally. This community service activity has a specific purpose as an effort to provide technical assistance to the planning of earthquake-resistant high-rise buildings by applying building planning rules in accordance with the applicable SNI code. Another aim is to support development efforts that are oriented towards educational activities and also places of community worship. The plan of activities carried out is in the form of studying the description of the location of the abdimas (site survey), modeling structural analysis, interpreting the results and providing recommendations for the results.